1996
DOI: 10.1111/j.1365-2958.1996.tb02647.x
|View full text |Cite
|
Sign up to set email alerts
|

The orlA gene from Aspergillus nidulans encodes a trehalose‐6‐phosphate phosphatase necessary for normal growth and chitin synthesis at elevated temperatures

Abstract: A cosmid carrying the orlA gene from Aspergillus nidulans was identified by complementation of an orlA1 mutant strain with DNA from the pKBY2 cosmid library. An orlA1 complementing fragment from the cosmid was sequenced. orlA encodes a predicted polypeptide of 227 amino acids (26360 Da) that is homologous to a 211-amino-acid domain from the polypeptide encoded by the Saccharomyces cerevisiae TPS2 gene and to almost the entire Escherichia coli otsB-encoded polypeptide. TPS2 and otsB each specify a trehalose-6-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 32 publications
5
46
0
1
Order By: Relevance
“…A comparison of the amino acid sequences of the tpsA and tpsB gene products does not provide a clue as to the reason for this. Interestingly, while this paper was prepared for publication, Borgia et al (43) reported on the presence of two trehalose-6-phosphate phosphatases in A. nidulans but did not investigate whether the two gene products may have different functions. It will be interesting to see if this is a general feature of multicellular fungi or a feature unique to aspergilli.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the amino acid sequences of the tpsA and tpsB gene products does not provide a clue as to the reason for this. Interestingly, while this paper was prepared for publication, Borgia et al (43) reported on the presence of two trehalose-6-phosphate phosphatases in A. nidulans but did not investigate whether the two gene products may have different functions. It will be interesting to see if this is a general feature of multicellular fungi or a feature unique to aspergilli.…”
Section: Discussionmentioning
confidence: 99%
“…In C. albicans, the tps2 mutant flocculates during stationary growth, while in A. nidulans, the mutant produces nonviable germination of spores through a deficiency in chitin production. Furthermore, both of these phenotypes can be suppressed by the addition of osmoprotectants to the culture medium (7,53,59). We did not observe a flocculation phenotype in a C. neoformans-like tps2 strain of C. albicans, but we did find different phenotypes between tps1 and tps2 mutants at low and high temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…T6P is an intermediate in trehalose biosynthesis that has been shown to possess regulatory potential (5,26 (7,21,22,47,53,59) and give further insights into T6P. In C. albicans, the tps2 mutant flocculates during stationary growth, while in A. nidulans, the mutant produces nonviable germination of spores through a deficiency in chitin production.…”
Section: Discussionmentioning
confidence: 99%
“…7). 27,[43][44][45] It was found that conidia from ÁsskA contained a significantly lower amount of transcript for each of these stress-tolerant or germination-associated genes. These results together support the view that SskA plays more sophisticated or wider roles in stress-tolerant spore development (Figs.…”
Section: Sska Is Implicated In Stress-tolerant Conidia Formationmentioning
confidence: 99%